2016
DOI: 10.1590/1983-21252016v29n310rc
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Ramularia Leaf Spot and Seed Cotton Yield in Different Sowing Times

Abstract: -The ramularia leaf spot (RLS) disease causes cotton yield losses. Choosing a less susceptible cultivar and a sowing time that are less favorable to the pathogen contribute to the management of this disease. The objective of this work was to evaluate the severity of ramularia leaf spot on cotton cultivars sowed in two different times. The experiment was conducted in a triple factorial design (4x3x2), consisted of four cultivars, the three thirds of the plant and two sowing times, with four replications. Each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…These results denote the importance of the chemical control and the destructive potential of the R. areola fungus, when this disease is not monitored or efficient control measures are not taken. These results confirm those found by Aquino et al (2008b) and Ascari et al (2016), who assessed the effects of fungicide application to control the ramularia leaf spot and observed increases of 88 % and 24.64 % in the cotton seed yield, respectively.…”
Section: Cotton Cultivarsupporting
confidence: 90%
See 3 more Smart Citations
“…These results denote the importance of the chemical control and the destructive potential of the R. areola fungus, when this disease is not monitored or efficient control measures are not taken. These results confirm those found by Aquino et al (2008b) and Ascari et al (2016), who assessed the effects of fungicide application to control the ramularia leaf spot and observed increases of 88 % and 24.64 % in the cotton seed yield, respectively.…”
Section: Cotton Cultivarsupporting
confidence: 90%
“…According to Johnson et al (2013) and Ascari et al (2016), the climate also affects the plant-pathogen interaction, as confirmed by the weather conditions recorded in the present study (Figure 1). …”
Section: Thirds Of the Plantsupporting
confidence: 88%
See 2 more Smart Citations
“…The cultivar FMT 707 had the lowest damage percentages, varying between 4.33 and 19.86% among disease gradients, followed by IAC 25, wherein damage percentages ranged from 10.24 to 25.08% (Table 2). Ascari et al (2016) has observed yield demages of 30.82% comparing control and uncontrol plots in first sowing. Cultivars had different ABSPC indexes and percentages of damage to productivity.…”
Section: Resultsmentioning
confidence: 94%